Alphataxin, a Small-Molecule Drug That Elevates Tumor-Infiltrating CD4+ T Cells, in Combination With Anti-PD-1 Therapy, Suppresses Murine Renal Cancer and Metastasis - Bristow, Cynthia L.; Reeves, Mary Ann B.; Winston, Ronald (Frontiers in Oncology, 2021)
By promoting the cytotoxic function of CD8+ T cells, immune checkpoint inhibitor therapy, e.g. programmed cell death protein-1 (PD-1), effectively inhibits tumor growth in renal cell carcinoma. Yet, as many as 87% of cancer patients do not respond to immune checkpoint therapy. Cytotoxic CD8+ T cell function integrally relies on CD4+ T helper cells. Remarkably, despite advances in immunotherapy, there are no pharmaceutical treatments that increase circulating CD4+ T cell counts. Nor has there been much attention given to tumor-infiltrating CD4+ T cells. Using data from a clinical trial (NCT01731691), we discovered that the protein alpha-1 proteinase inhibitor (α1PI, alpha-1 antitrypsin) regulates the number of circulating CD4+ T cells. The orally available small-molecule drug Alphataxin targets this pathway. We aimed to examine how Alphataxin affected tumor growth in a murine model of renal cell carcinoma. Alphataxin, in combination with anti-PD-1 antibody, significantly elevated the ratio of circulating and tumor-infiltrating CD4+ T cells. In one study, following orthotopic implantation of syngeneic renal adenocarcinoma cells, combination treatment resulted in 100% regression of tumor growth. Moreover, in mice implanted orthotopically with one log more tumor cells, doubling Alphataxin dose in combination treatment led to 100% regression in one-third of mice and 81% suppression of tumor growth in the remaining two-thirds of mice. Lung metastasis was present in monotherapy, but significantly reduced in combination-treated mice. Orally available Alphataxin, the first and only drug developed to increase CD4+ T cells, in combination with anti-PD-1, is a powerful therapeutic method that provides long-term remission in renal cell carcinoma and potentially other T cell-responsive cancers by increasing the number of CD4+ tumor-infiltrating T cells.